The treatment of hypertension in care home residents: a systematic review of observational studies - Welsh, Tomas; Gladman, John R.F.; Gordon, Adam L. (Elsevier, 2014)
Aim: To describe the prevalence of hypertension in care home residents, its treatment, change in treatment over time, and the achievement of blood pressure (BP) control. Method: The PubMed, Cochrane, Embase, and PsychINFO databases were searched for observational studies involving care home residents with a diagnosis of hypertension. The search was limited to English language articles involving adults and humans published from 1990 onward. Abstracts and titles were reviewed with eligible articles read in full. Bibliographies were examined for further relevant studies. The final selection of studies was then analyzed and appraised. Results: Sixteen articles were identified for analysis, of which half were studies carried out in the United States. The prevalence of hypertension in care home residents was 35% (range 16%e71%); 72% of these were on at least 1 antihypertensive (mean 1.5 antihypertensives per individual), with diuretics being the most common. The prevalence of hypertension in study populations was greater in more recent studies (P ¼ .004). ACEi/ARBs (P ¼ .001) and b-blockers (P ¼ .04) were prescribed more frequently in recent studies, whereas use of calcium-channel blockers and diuretics remained unchanged over time. The number of antihypertensives prescribed per patient was higher (correlation 0.332, P ¼ .009), whereas fewer patients achieved target BP (correlation 0.671, P ¼ .099) in more recent studies. Conclusion: Hypertension is common in care home residents and is commonly treated with antihypertensive drugs, which were prescribed more frequently in more recent studies but with no better BP control. These studies indicate a tendency toward increasing polypharmacy over time, with associated risk of adverse events, without demonstrable benefit in terms of BP control. Copyright 2014 - American Medical Directors